Organizational learning and development from an evidence base - Kearns, Paul (Routledge, 2015)
t is now widely accepted that organizational maturity is dependent on being able to reorganize on a continuous basis and learn faster and more effectively than your competitors. Organizations that want to be sure they are competing at the highest level need clear indicators that their organizational learning and development capability is fully functional. This new book by Paul Kearns focuses on the need for an evidence-based approach to learning and development, bringing together the author's extensive knowledge of HRM and organizational learning with new developments in the field